RCB initiates Arabidopsis thermomorphogenesis by stabilizing the thermoregulator PIF4 in the daytime - Yongjian Qiu (Nature Portfolio, 2021)
The Arabidopsis PIF4 transcription factor is stabilized during the daytime in response to warm temperature and regulates thermomorphogenesis. Here the authors show that the response to warm temperature depends on the concerted action of the HMR and RCB proteins that act collaboratively to stabilize PIF4.